(untitled) (Innovation & Development in Engineering and Applied Science, 2021)
The mechanical design of a rehabilitator with which active-passive knee joint therapy can be combined is presented. Two solution alternatives based on anatomical, physiological and therapeutic characteristics of the joint are proposed. Analyzing the established criteria, the best alternative is chosen. The anthropometric characteristics of an average adult were considered for the sizing of the equipment. Weight, strength and cost criteria were considered in the development of the material selection stage. Subsequently, a study of stresses and displacements was carried out using a computational program, based on the finite element method, estimating actual operating conditions. To carry out this process load conditions and restrictions were established considering the actuation associated with the movements and amplitude of these (maximum angles) of knee under normal condition. Finally, the operating conditions were checked based on the safety factor of the structural components confirming the ability to withstand the established operating scenarios.